(untitled) (Asian Journal of Social Science Studies, 2022)
The history of immigration is intrinsically related to the growth of Beijing Opera in Singapore. Since the turn of the century, as China’s economy has continued to grow, a growing number of Chinese living abroad have started to seek out familiar Chinese voices and deepen their links to the nation. In The Tian Yun Beijing Opera Society aggressively welcomes new immigrants while also assuming the duty of youth development. The overseas Chinese young are now dealing with difficult cultural adaptation and identity crises as a result of postmodernism and the internet information age. The Tian Yun Beijing Opera Society is actively fostering a new generation of Beijing Opera enthusiasts by encouraging secondary school students to study the opera and establishing a youth acting clubs. This makes Beijing Opera an essential link in fostering the development of overseas Chinese cultural communities and strengthening ethnic group cohesion.